Trends in ExPEC serogroups in the UK and their significance - Ciesielczuk, H. (Eur J Clin Microbiol Infect Dis, 2016)
Extra-intestinal pathogenic Escherichia coli are a significant cause of urinary tract infection and bacteraemia within the UK. We sought to identify the serogroups of 658 E. coli isolates collected in the UK between January 2011 and March 2012, to better understand the ExPEC population and understand the relevance of serogroups in this pathotype. Isolates were typed and serogroup identified using established phenotypic and molecular methods. Sixty-two serogroups were identified; 54 among urinary isolates and 35 among bloodstream isolates. However, serogroups O25, O6, and O2 dominated both infection types. These serogroups were linked to the major ExPEC STs as follows: ST131-O25, ST73-O6, ST127-O6, and ST95-O2. The serogroup data from this study have increased our understanding of the ExPEC population in the UK, but also highlighted key ST–serogroup relationships within the major ExPEC clones. These data can be used to guide vaccine design and in the development of laboratory diagnostic tests targeting the ExPEC population.